The potential role of Peperomia pellucida (l.) Kunth in ameliorating hyperglycaemic and glycation-induced inflammation in human retinal pigment epithelial cell line (ARPE-19) - Ho, Keat Lam (2025)
Diabetic retinopathy (DR) is a microvascular complication that causes blindness. DR management is costly and accompanied with adverse effects. Peperomia pellucida (L.) Kunth is traditionally used for inflammation, but its effects on DR remain unexplored. This study aimed to elucidate the regulatory mechanism of P. pellucida against high glucose and glycation induced stress in human retinal pigment epithelial cell line (ARPE-19). P. pellucida was macerated with methanol, and fractionated with hexane, chloroform, ethyl acetate, n-butanol and water. Semi-quantitative colorimetric assays indicated that the ethyl acetate plant fraction demonstrated potent antioxidant, anti-inflammatory and anti-glycation activities, alongside significant (p<0.05) higher α-amylase and α-glucosidase inhibitory activities when compared to the standard anti-diabetic drug, acarbose. Both ethyl acetate fraction and crude methanolic plant extract significantly (p<0.05) restored the ARPE-19 cell viability under high glucose and glycation stress. High glucose and glycation induced the nuclear factor kappa B (NF-κB) p65 and signal transducer and activator of transcription 3 (STAT3) signalling pathways with significant (p<0.05) increase of gene (1.22-31.30 folds) and protein (1.39-7.79 folds) expression for angiogenic and inflammatory markers, including interleukin 8 (IL-8), matrix metalloproteinase 2, monocyte chemoattractant protein 1, receptor for AGE, and vascular endothelial growth factor in ARPE-19, as determined via reverse transcription real-time polymerase chain reaction and western blot. Conversely, the gene and protein (0.12-0.56 folds) expression of glutathione peroxidase were significantly reduced due to the suppression of peroxisome proliferator-activated receptor gamma (PPAR-γ). P. pellucida did not alter the biomarkers’ gene and protein expression under normal glucose condition except for IL-8 (0.75-0.89 folds). Although in vivo brine shrimp toxicity analysis revealed that crude methanolic extract and ethyl acetate fraction were mildly toxic, in vitro cell viability findings showed that they were non-cytotoxic towards ARPE-19. Dillapiole, 2,4,5-trimethoxystyrene, β-caryophyllene, β-santalene, methyl 9-octadecenoic acid and methyl pheophorbide-a were among the predominant phytochemicals identified in the crude methanolic extract via spectroscopic and spectrometric techniques. Notably, methyl pheophorbide-a was identified for the first time in P. pellucida. The current findings support P. pellucida as an alternative therapeutic source to mitigate high glucose and glycation-induced stress in DR by regulating the NF-κB p65, PPAR-γ and STAT3 signalling pathways.